Effect of vitamin E administered to men in infertile couples on sperm and assisted reproduction outcomes: a double-blind randomized study - Roberto Matorras, M.D., Ph.D; Jairo Pérez-Sanz, Ph.D; Beatriz Corcóstegui, Ph.D; Irantzu Pérez-Ruiz, Ph.D; Iker Malaina, B.S., Ph.D; Sara Quevedo, B.S; Fermín Aspichueta, Ph.D; Lorena Crisol, Ph.D; Lorea Martinez-Indart, B.S; Begoña Prieto, M.D., PhD; Antonia Expósito, Ph.D (Elsevier, 2020)
Objective: To evaluate the influence on sperm parameters and in vitro fertilization (IVF) outcomes of the administration of 400 mg/day of vitamin E for 3 months to men from infertile couples who are undergoing IVF. Design: Double-blind, placebo-controlled, randomized study. Setting: Human reproduction unit of a university hospital. Patient(s): A total of 101 couples, 50 in the vitamin E group and 51 in the placebo group, undergoing IVF, among whom 64.4% of cases had an abnormal spermiogram according to World Health Organization (WHO) criteria. Intervention(s): Vitamin E (α-tocopherol), 400 mg daily by mouth for 3 months, with sperm analysis performed immediately before starting the treatment and 3 months later on the day of IVF. Main Outcome Measure(s): WHO sperm parameters and IVF outcomes. Result(s): Although there was a statistically significant increase in progressive motility in the vitamin E group compared with before-treatment values, a similar increase occurred in the placebo group. Normal morphology was even better in the placebo group. Regarding IVF outcomes, better fertilization rates were observed in the placebo group, but the live-birth rate per transfer was statistically significantly higher in the vitamin E group: 17 (41.46%) of 41 versus 9 (20.46%) of 44 in the placebo group. Although the clinical pregnancy rates (both per transfer and per cycle started) and the implantation rate were somewhat higher in the vitamin E group (43.9% and 25%; 36.0% and 22.0%; and 24.7% and 14.1%, respectively), the increase was not statistically significant. Conclusion(s): The effect of vitamin E on classic sperm parameters was not an improvement over placebo. Nonetheless, vitamin E administration was associated with a statistically significantly higher live-birth rate, and there was a trend toward better results in other IVF parameters. Clinical Trial Registration Number: Eudra CT 2007-000960-25.